The SD3 Measure of Narcissism and the Narcissism of the NARC Model: Differences and Similarities - Gojković, Vesna; Plahuta, Marija; Dostanić, Jelena (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Divergent status of Narcissism vis-à-vis two other Dark Triad traits with respect to correlations with different psychosocial outcomes has suggested the need for a multidimensional approach to its conceptualisation and measurement. Here we have investigated a) whether and how Admiration and Rivalry (the two dimensions of the dichotomous NARC model of grandiose narcissism) fit in the same measurement domain with the Dark Triad traits; and b) the predictive value of all five traits relative to religiosity, as an indication of prosocial outcome. Our findings suggest that Admiration is the brightest, and Rivalry and Psychopathy are the darkest, elements of the latent dimension encompassing all traits defined by the SD3 and NARQ psychometric scales. The SD3 measure of Narcissism was the only trait predictive of religiosity. The data suggest that vicinity to Psychopathy is the key evidence for the trait’s antagonistic nature, and that future scrutiny of the SD3 measure of Narcissism is acutely needed.